Compressive Strength Analysis of Mortar Made from Volcanic Sand in Nagari Aia Angek Based on Magnetic Mineral Content - Amirullah, Fajar Fikri; Hamdi, -; Dwiridal, Letmi; Amir, Harman; Syafriani, -; Ratnawulan, - (PILLAR OF PHYSICS, 2024)
Mortar is a binder or adhesive with a standard viscosity of ingredients (water, cement, and sand). Mortar made has strength, mortar strength is measured using Cement Compression testing machine. Sand in mortar making contains magnetic minerals such as magnetite (Fe3O4) or Fe2+3Fe+2O4-2, hematite mineral (α-Fe2O3) which will be measured for magnetic susceptibility value using Bartington Magnetic Susceptibility Meter Sensor Type B (MS2B). To determine the concentration of magnetic minerals and their relationship with mortar compressive strength, the rock magnetism method was used. Measurement of sand samples of Kamumuan River, Sungai Limau District using Bartington Magnetic Susceptibility Meter Sensor Type B (MS2B) by categorizing sand into 3 treatment, namely Addition of magnetic minerals (PTM) with χLF value 3863.3 x 10-8m3/kg and χFD (%) 0.72, reduction of magnetic minerals (PKM) with χLF value 1920 x 10-8m3/kg and χFD (%) 0.79, normal magnetic minerals (PM) with χLF value 2334.7 x 10-8m3/kg and χFD (%) 0.62. The sample has a grain type that is almost no superparamagnetic grain and has antiferromagnetic properties. Samples grouped by treatment were made into mortar and tested using a cement compression testing machine with the results of mortar compressive strength, namely ATM of 49.4 Kg/cm², AKM of 46.6 Kg/cm², and AM 52.3 Kg/cm². Based on the analysis conducted, the magnetic minerals contained in the sand affect the results of the compressive strength of the mortar, the higher the susceptibility value in the sand, the stronger the compressive strength of the mortar